ANALISIS PERLINDUNGAN KONSUMEN TERHADAP HILANGNYA BAGASI TERCATAT PENUMPANG MASKAPAI LION AIR - NIM. A1011211140, CAROLINSKA ANGELA JESSICA (Jurnal Fatwa Hukum, 2025)
AbstractThis study aims to analyze whether the current regulations regarding checked baggage have protected the safety of Lion Air passengers' goods and what legal remedies are taken by Lion Air passengers for the loss of checked baggage. Using normative legal methods and a legislative approach and a case approach, then analyzed qualitatively to understand the existing regulations and the dispute resolution practices that occur. The results of the study indicate that in the Minister of Transportation Regulation Number 77 of 2011 concerning the Responsibility of Air Transport Carriers, the provisions on the amount of compensation for the loss of checked baggage of passengers in practice do not correspond to the real value of the losses experienced by passengers. Legal remedies that can be taken by Lion Air passengers for the loss of checked baggage are divided into legal remedies through litigation and non-litigation. However, in practice, Lion Air passengers who have received compensation for the loss of checked baggage do not take any legal remedies, even though the compensation creates a sense of injustice for passengers. Furthermore, it is recommended that airlines improve the quality of their services, the government can supervise airlines and review applicable regulations, and consumers can report and file lawsuits in court.Keywords: Consumer Protection, Checked Baggage, Lion Air Airlines.  AbstrakPenelitian ini bertujuan untuk menganalisis apakah peraturan mengenai bagasi tercatat saat ini telah melindungi keselamatan barang penumpang maskapai Lion Air dan bagaimana upaya hukum yang dilakukan oleh penumpang Lion Air atas hilangnya bagasi tercatat tersebut. Dengan menggunakan metode yuridis normatif dan pendekatan perundang-undangan dan pendekatan kasus, kemudian dianalisis secara kualitatif untuk memahami peraturan yang ada serta praktik penyelesaian sengketa yang terjadi. Hasil penelitian menunjukkan bahwa dalam Permenhub Nomor 77 Tahun 2011 Tentang Tanggung Jawab Pengangkut Angkutan Udara, ketentuan besaran ganti kerugian atas hilangnya bagasi tercatat penumpang dalam praktiknya tidak sesuai dengan nilai rill kerugian yang dialami oleh penumpang. Upaya hukum yang dapat diambil oleh penumpang Lion Air atas hilangnya bagasi tercatat, terbagi menjadi upaya hukum melalui jalur litigasi dan non litigasi. Tetapi, pada praktiknya penumpang Lion Air yang telah mendapatkan ganti kerugian atas hilangnya bagasi tercatat tersebut tidak melakukan upaya hukum apapun, meskipun ganti kerugian tersebut menimbulkan rasa ketidakadilan bagi penumpang. Selanjutnya, disarankan agar maskapai penerbangan meningkatkan kualitas layanan, pemerintah dapat mengawasi maskapai dan memperkaji ulang peraturan yang berlaku, serta bagi konsumen dapat melakukan pelaporan dan mengajukan gugatan ke pengadilan.  Kata Kunci: Perlindungan Konsumen, Bagasi Tercatat, Maskapai Lion Air.